Tratamiento endodóntico de un absceso Alveolar agudo: Reporte de un caso clínico - Garcia Zamarron, Diana Juana (2020)
https://www.revista-portalesmedicos.com/revista-medica/tratamiento-endodontico-de-un-absceso-alveolar-agudo-reporte-de-un-caso-clinico/